Historical Perspective of the Addition of Magnetic Nanoparticles Into Anaerobic Digesters (2014-2021) - Casals, Eudald; Barrena, Raquel; Gonzalez, Edgar; Font, Xavier; Sánchez, Antoni; Puntes, Victor (Frontiers in Chemical Engineering, 2021)
The addition of magnetic nanoparticles to batch anaerobic digestion was first reported in 2014. Afterwards, the number of works dealing with this subject has been increasing year by year. The discovery of the enhancement of anaerobic digestion by adding iron-based nanoparticles has created a multidisciplinary emerging research field. As a consequence, in the last years, great efforts have been made to understand the enhancement mechanisms by which magnetic NPs addition enhances the anaerobic digestion process of numerous organic wastes. Some hypotheses point to the dissolution of iron as essential iron for anaerobic digestion development, and the state of oxidation of iron NPs that can reduce organic matter to methane. The evolution and trends of this novel topic are discussed in this manuscript. Perspectives on the needed works on this topic are also presented.